PERSEPSI PESERTA DIDIK TERHADAP PEMBELAJARAN BERBASIS DARING - Nicky Dwi Puspaningtyas; Putri Sukma Dewi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
Online learning is a solution in the era of the COVID-19 pandemic. However, of course, in the implementation, there must be many difficulties for both teachers and students. This study aims to describe students' perceptions of online learning in Lampung Province. Samples were randomly selected using the Slovin Method with a population of Senior High School students in Lampung Province. 400 students from more than 25 schools were chosen for this study. The sample is given a perception questionnaire that has been tested for validity and reliability which is made on Google Form. Based on the research results, it can be concluded that students get good support from various parties in implementing online learning. However, the majority of students experienced problems related to signals during online learning. Many students also have not been able to master the learning application well so that it will affect the learning process. In addition, students stated that they had difficulty communicating with the teacher and preferred to have face-to-face discussions and students had difficulty understanding the material if it only came from books.